Biomechanical justification of the choice of optimum mode for passing the individual pursuit race - A.N. Kolumbet; L.Y. Dudorova; N.A. Babina; S.G. Natroshvili; S.M. Chernovsky (Physical Education of Students)
Purpose : biomechanical justification of the choice of optimum mode of passing competitive distance of 4 km individual pursuit on track. Material : The qualified cyclists (n=14) participated in researches. The modified stationary cycle Monark was used. Cyclists performed work in two modes - A and B. Results : The mode B is physiologically more favorable. The mode B should be considered as a model of passing a distance in preliminary races of individual pursuit. Work in the mode A demands terminal mobilization of organism functions. Work in the mode A is more effective in the achievement of sports result. It can be used only once in the final race of competitions. Conclusions : The received data should be considered as a demonstration of specific features of passing a distance in the competitive modes. The tactical variant of competitive program creation is defined by the individual functional state.